VR:n Pasilan konepaja - Ukkonen, Paul A.
sisällön kuvaus: VR:n Pasilan konepaja. Talvinen näkymä pihalta, jossa junavaunuja.
Keywords: konepajat; rakennukset; kiskot; puut; junavaunut; Valtionrautatiet; Suomi, Uusimaa, Helsinki, Vallila Helsinki, Aleksis Kiven katu